Da adoção como último recurso à entrega voluntária: um estudo de caso em Imperatriz-MA - VIANA, Jáina Lopes (2024)
The present study aimed to analyze the dynamics of child circulation in Imperatriz, Maranhão, focusing on the judicial processes of the Juvenile Court between 2019 and 2023. This investigation arose from the observation that, in addition to formal legal norms and procedures, there is an informal practice that governs the circulation of these children. Often, biological families directly hand over their children to adoptive families without the mediation of the judiciary. The research examined ninety-seven cases, sixty-six of which were Adoptions from the Registry and thirty-one were Adoptions Outside the Registry with Termination of Parental Rights. Three of these cases were analyzed as case studies, and we presented an “addendum” that reveals recent changes in circulation dynamics to understand how and why these children circulate outside the system. The analyses of these studies are anchored in the theories of Claudia Fonseca (2006) on child circulation, Howard Becker (2008) on deviance, and Erving Goffman (1982) on stigma. The case studies, focusing on processes of "adoption à brasileira," intuitu personae adoption, registry adoption, and voluntary surrender, revealed that biological families, for the most part, reside in peripheral areas and face social, economic inequalities, and stigma. The research also explored the social and state reasons behind this phenomenon. It was found that the circulation of children before the conclusion of the legal process can be seen as a reflection of state abandonment in some situations, which may contribute to mothers opting to surrender their children. This study employed both qualitative and quantitative methodologies, including semi-structured interviews, direct observation, document analysis, participant observation, and field notes, in addition to statistical analysis to investigate the complexity of these social dynamics.